Mencius and Xunzi on Xing (Human Nature) - Sung, Winnie (2020)
This article introduces and analyses the debate between Mencius and Xunzi on xing 性 (human nature). While Mencius claims that xing is good, Xunzi claims that xing is bad. A common way of interpreting these two different claims is to determine the scope of xing. It is generally agreed that, for Mencius, it is the heart/mind that falls within the scope of xing, for Xunzi, the sensory desires. This article also explores a different way of approaching Mencius's and Xunzi's different claims about xing. It is suggested that Mencius's and Xunzi's different views on xing can be understood in terms of their different views on the heart/mind (xin 心). While Mencius thinks that the heart/mind has a morally good natural tendency, Xunzi thinks that the heart/mind has a morally problematic tendency.